Analisis Aplikasi Konsep Arsitektur Berkelanjutan pada Gedung Kantor (Studi Kasus Gedung Kantor Samsat 2 Banjarmasin) - Ismail, Fachriady; Rahman, Akbar; Febrita, Yuswinda (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
Buildings are one of the causes of global warming and should be designed with sustainability in mind. Office buildings are particularly important, as they support economic sustainability. Office buildings need to be designed with strategies to achieve green buildings and align with the principles of Sustainable Architecture, as environmental friendliness contributes to curbing global warming by improving the microclimate. A descriptive qualitative research method was employed through field observations, interviews with architects and building managers, and secondary data analysis from documentation, reports, library studies, and related literature. The purpose of this research is to understand the concept of Sustainable Architecture and to analyze and understand the extent to which the concept has been applied to the case study buildings. Further research analysis can draw conclusions by defining the principles of Sustainable Architecture contained in theoretical studies on office buildings, while still considering user needs and comfort, as well as operational costs. This research is expected to increase knowledge related to Sustainable Architecture, thereby contributing to the design of office buildings that are environmentally friendly and provide comfort to building users.